Biology of Black Soldier Fly (Hermetia illucens) and Utilization of its Waste (Maggot Frass) for Plant Growth: A Literature Review - Idris, Muhammad; Rismayani, Dessy; Aulia, Annisa; Nopiyanti, Tita; Rahayu, Resti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The utilization of maggot frass from Black Soldier Fly (BSF) larvae (Hermetia illucens Linneus, 1875) has garnered attention in the context of organic farming as a promising alternative to enhance plant growth and development. Maggot frass, a byproduct of the larval digestion process, is rich in essential nutrients such as nitrogen, phosphorus, potassium, and contains beneficial microorganisms for the soil. This study employs a literature review method. Literature sources were obtained from the Google Scholar database using keywords such as